Simultaneous synthesis and consolidation of a nanocrystalline 17.14Fe(0.7)Cr(0.2)Al(0.1)-Si3N4 composite by pulsed current activated heating - Shon, In-Jin; Du, Song-Lee; Ko, In-Yong; Song, Chul-Gyu; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Sang-Whan (KOREAN ASSOC CRYSTAL GROWTH, INC, 2012)
Nanopowders of Fe3N, Cr, Si and Al powders were fabricated by high-energy ball milling. A high-density nanocrystalline 17.14Fe(0.7)Cr(0.2)Al(0.1)-Si3N4 composite was simultaneously synthesized and consolidated by a pulsed current activated sintering (PCAS) method within two minutes from mechanically activated powders of Fe3N, Cr, Si and Al. The advantage of this process is that it allows very quick densification to near theoretical density and prohibits grain growth in nano-structured materials. The hardness of the composite was about 430 kg/mm(2).
Keywords: SILICON-NITRIDE; CERAMICS; BEHAVIOR; POWDERS; METALS; WC